Управління конкурентоспроможністю регіону на засадах смарт-спеціалізації - Мисько, Олена Віталіївна; Mysko, Olena (ЦНТУ, 2024)
Метою кваліфікаційної роботи виступає проведення дослідження та обґрунтування важливості розумної спеціалізації для підвищення регіональної конкурентоспроможності. Крім того, метою є сформулювати рекомендації щодо підвищення конкурентоспроможності регіону шляхом впровадження розумної спеціалізації. Досягнення цієї мети залежить від вирішення таких завдань: вивчити поняття «конкурентоспроможність» і «регіональна конкурентоспроможність»; дати визначення поняття «розумна спеціалізація»; дослідити методи управління конкурентоспроможністю за допомогою розумної спеціалізації; дослідити конкурентоспроможність регіону на основі розумної спеціалізації; проаналізувати впровадження інтелектуальної спеціалізації в стратегію регіонального розвитку; оцінити передумови розумної спеціалізації в українських регіонах; оцінити готовність Кіровоградської області до смартспеціалізації; здійснити розробку стратегій і підходів для посилення управління конкурентоспроможністю за допомогою розумної спеціалізації; проаналізувати міжнародний досвід розумної спеціалізації; дослідити реалізацію в Україні концепції розумної спеціалізації; сформулювати дорожню карту підвищення конкурентоспроможності Кіровоградської області шляхом розумної спеціалізації. Об’єктом дослідження є регіони України. Предмет дослідження – це аналіз процесів і процедур управління, які безпосередньо впливають на рівень конкурентоспроможності регіону. The purpose of the qualification work is to conduct research and substantiate the importance of smart specialization for increasing regional competitiveness. In addition, the goal is to formulate recommendations for increasing the competitiveness of the region through the implementation of smart specialization. Achieving this goal depends on solving the following tasks: to study the concepts of "competitiveness" and "regional competitiveness"; define the concept of "smart specialization"; explore methods of managing competitiveness through smart specialization; to investigate the competitiveness of the region based on smart specialization; to analyze the implementation of intellectual specialization in the strategy of regional development; assess the prerequisites for reasonable specialization in Ukrainian regions; assess the readiness of the Kirovohrad region for smart specialization; develop strategies and approaches to strengthen competitiveness management through smart specialization; analyze the international experience of smart specialization; to investigate the implementation of the concept of smart specialization in Ukraine; formulate a road map for increasing the competitiveness of the Kirovohrad region through smart specialization. The object of the study is the regions of Ukraine. The subject of the study is the analysis of management processes and procedures that directly affect the level of competitiveness of the region.
Management the competitiveness of the region on the basis of smart specialization
Keywords: регіон; управління; рейтинг; region; management; rating